Anti-inflammatory treatment improves high-density lipoprotein function in rheumatoid arthritis. Issue 10 (16th November 2016) - O'Neill, Francis; Charakida, Marietta; Topham, Eric; McLoughlin, Eve; Patel, Neha; Sutill, Emma; Kay, Christopher W M; D'Aiuto, Francesco; Landmesser, Ulf; Taylor, Peter C; Deanfield, John
Abstract : Objective: Patients with rheumatoid arthritis (RA) are at increased cardiovascular risk. Recent studies suggest that high-density lipoprotein (HDL) may lose its protective vascular phenotype in inflammatory conditions. However, the effects of common anti-inflammatory treatments on HDL function are not yet known. Methods: We compared the function of HDL in 18 patients with RA and 18 matched healthy controls. Subsequently, patients were randomised to (methotrexate+infliximab (M+I) (5 mg/kg)) or methotrexate+placebo (M+P) infusions for 54 weeks. At week 54 and thereafter, all patients received infliximab therapy until completion of the trial (110 weeks), enabling assessment of the impact of 1 year of infliximab therapy in all patients. HDL functional properties were assessed at baseline, 54 weeks and 110 weeks by measuring the impact on endothelial nitric oxide (NO) bioavailability and superoxide production (SO), paraoxonase activity (PON-1) and cholesterol efflux. Results: All HDL vascular assays were impaired in patients compared with controls. After 54 weeks, NO in response to HDL was significantly greater in patients who received M+I compared with those who received M+P. Endothelial SO in response to HDL was reduced in both groups, but PON-1 and cholesterol efflux remained unchanged. All vascular measures improved compared with baseline after ≥1 infliximab therapy in the analysis at 110 weeks. No significant trend was noted for cholesterol efflux. Conclusions: HDL function can be improved with anti-inflammatory treatment in patients with RA. The M+I combination was superior to the M+P alone, suggesting that the tumour necrosis factor-α pathway may have a role in HDL vascular properties.